The obstetric family tradition at the Real Colegio de Cirugía de San Carlos de Madrid: Concepción de Navas, the daughter of Juan de Navas - María Dolores Ruiz-Berdún (Universidad de Alicante, 2012)
This article basically, studied the documentation which is preserved in the archive of the Universidad Complutense de Madrid and the Archivo Histórico Nacional concerning to the family Navas. Juan de Navas was an eminent surgeon of end of century XVIII, author of Elementos del arte de partear, ending his professional career as Vice - Director of the Real Colegio de Cirugía de San Carlos de Madrid. In this centre, a few years later, his daughter Concepción de Navas studied midwifery. This research delves into the figure of these two health professionals and shows the harsh conditions of life for the professional practice existing in Madrid in the 18th and 19th centuries.